Determination of Gold in e‐Waste Dust Samples and Geological Matrices by ICP‐MS after Extraction by an HClO4‐HBr‐HI‐Aqua Regia Mixture. Issue 2 (8th September 2015) - Strnad, Ladislav; Šebek, Ondřej; Fayadová, Marie; Vrba, Jan
Abstract : This study describes two methods (Procedures‐1 and ‐2) for the direct extraction of Au by an inorganic acid mixture (HClO4 ‐HBr‐HI‐ aqua regia ) from complex sample matrices. Standard PTFE jars at 200 °C were used to decompose test portions of 0.5–1 g, with subsequent precise and accurate analysis by ICP‐MS without any other preconcentration or separation. Procedure‐1 decomposed samples effectively without the necessity of leaching with HF and was developed for dust samples from e‐waste (electronic waste) processing; however, testing on geological reference materials showed very good results. The analyses of replicate decompositions ( n = 5) from both procedures yielded very good precision (< 5% RSD) for most of the reference materials. The accuracy achieved was better than ± 10%, with the exception of NIST SRM 2782 data from Procedure‐1. Two unknown samples of dust from e‐waste processing (P‐1 and VM‐1) exhibited elevated concentrations of Au (21.31–61.64 μg g −1 ) with precision better than 10% ( n = 5). The proposed techniques are simple, sensitive and sparing in the use of chemicals, and are designed for a variety of e‐waste dust samples. No significant influences were observed for the predicted spectral interferences on mass 197 Au. Key Points: The direct extraction of Au by inorganic acid mixture (HClO4 ‐HBr‐HI‐ aqua regia ) Application to anthropogenic and geological matrices Precise solution ICP‐MS analysis.